Digestive morpho-physiology and energy requirements of mud crab Scylla serrata larvae - Lumasag, Gil J. (Miagao, Iloilo University of the Philippines in the Visayas, 2006)
Studies on the development of the feeding apparatus, onset of digestive enzymes and energy requirements under fed and starved conditions were conducted on the mud crab Scylla serrata larvae. The mandibles were highly denticulated, with well-defined teeth at the incisor and molar processes designed for triturating food at zoeae stages. These became simple in structure becoming shield-shape ideal for cutting food at megalopa stage, coupled with the apperance of mandibular palp. Endopods of accesory feeding apparatus such as the maxillules, maxilla, first maxillipeds, second maxillipeds have increased number of setae as the larvae grew, with the appearance of the third maxillipeds at megalopa. The foregut at early zoea appeared as simple cavity but becme a double chamber t zoea 3 with the development of the gastric mill. Full development of the gastric mill was observed at megalopa. Histochemical localiztion of the digestive enzymes such s amylase, lipase and protease had shown that they were already present at early zoea and with profound expressions at later stages of the larvae. They were localized at the midgut and midgut glands and found negative at the esophagus and foregut. Zoeae i fed with Brachiomus rotunddiformis for 72 hours increased in weight by more han five times while unfed larvae lost about 35.3% of their original weight. Starved larvae when fed had increasing trnd of ingestion rates shown by zoea previously starved from 0 to 24 hours but decreasing rates of ingestion by those starved beyond 24 hours LT 50 of unfed larvae occured 2.7 to 2.9 days after hatching and zoea 1 unfed for 36 and 48 hours had PNR50 at 24 and 12 hours after feeding, respectively. Lipid was the source of energy of larve during unfed conditions with carbon and nitrogen ratios decreasing with increase in starvation time. Fatty acids generally decreased starting at 12 hours of unfed conditions of the zoea with most unsaturated fatty acids fullt depleted as early as 24 hours of unfed conditions. The significance of these findings is discussed in planning effective feeding management of the mud crab larvae.
Dissertation (Doctor of Philosophy in Fisheries-Aquaculture) - University of the Philippines in the Visayas, January 2006.
Dissertation (PhD in Fisheries-Aquaculture) -- Miagao, Iloilo :U.P. in the Visayas, January 2006.
Keywords: Mud crab -- Energy requirements; Mud Crab (Scylla serrata)